Social capital and job search behaviour of long-term welfare recipients. Issue 11 (12th October 2015) - Varekamp, Inge; Knijn, Trudie; van der Gaag, Martin; Bos, Peter
Abstract : Purpose: – Long-term welfare recipients in the Netherlands are either long-term unemployed or part-time employed in jobs that generate incomes below the subsistence level. The question is whether reintegration policies aiming at their return to – a fulltime – job should consider individual social network factors besides psychological and human capital factors. The purpose of this paper is to investigate welfare recipients' job search behaviour, in particular how individual social capital is distributed, and whether it is related to job search activities. Design/methodology/approach: – Standardised and structured interviews were conducted with 189 long-term unemployed welfare recipients. An adapted version of the Resource Generator instrument was used to measure individual access to social capital. Findings: – Social capital scales measuring domestic social resources, status-related social resources, expert advice on regulations and financial matters, and advice on finding a job were developed and psychometrically tested. Status-related social resources were more easily accessible to men and higher educated persons. Advice on finding a job was more easily accessible to recently unemployed individuals. Domestic social resources were less accessible to ethnic minorities. Persons with more social capital, specifically status-related social resources and advice in finding a job, showed more active job search behaviour. Social implications: – The differences in job search activities between respondents with more social capital and those with less social capital were present but to a small degree, and therefore there is no argument for reintegration activities to focus on enlarging social capital. Originality/value: – This study addresses the instrumental functions of the social network by multidimensionally scrutinising the resources that social relationships provide access to.